Profile of centers for independent living based on the National CIL Management Database. - Tomita MR; Moffat M; Usiak DJ; Moffat J (Journal of Vocational Rehabilitation, 2004)
In order to create the first comprehensive National CIL Management Database of existing CIL programs, services, management structures and funding resources, data from 255 CILs was collected through mailed surveys. The total revenue of this industry was over $218.5 million, employing over 4,800 people and offering services and programs to more than 188,000 people with disabilities. A developmental pattern was identified which was similar to other organizations. Further studies were encouraged.